The Incidence of Contrast Induced Nephropathy-Acute Kidney Injury after cardiac catheterization in Basra Cardiac Catheterization Center. A Prospective Cohort Study - Alhasan Mujtaba1, Mohammed Abbas Taher1, Hayder Kadhum AlRubay2, Mazin Abed Hazza3, Hasan Mohammed A (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Patients who opt for coronary interventions to help them with their IHD problems face several adverse reactions; the most frequently faced is acute kidney injury from contrast media exposure or contrast induced nephropathy. Those patients have higher mortality and morbidity both in the short and longterm period. The incidence of this adverse reaction in Al-Basra Cardia Center is poorly studied so far. We measured the incidence of AKI in this center and tried to correlate the risk with some important covariates identified by previous researches. Method: this was an observational prospective study. It was a part of the double blind single center study (the effect of spironolactone on the incidence of AKI in patients with Stable IHD admitted for coronary intervention, trial registration: ClinicalTrials.gov NCT03329443). Results: The overall incidence of CIN was 20.2% in this cohort sample. Priori defined high risk variables were tested in univariate logistic regression, and if found to be significant they were to be added to a Multi-Logistic regression model analysis. In Regression analysis only GFR (Log Odds ratio) [0.984 (0.971-0.998)] and Mehran Risk score [Mehran >6 (2.456(1.335-4.519), Mehran >11 (3.931) Mehran >16 (12.366) compared to Mehran <5) were positive in the model analysis. Conclusion: there seems to be a high incidence of AKI in this cohort. Important significant factors include low GFR and a good correlation with Mehran risk score.